Candidate gene discovery for salt tolerance in rice (Oryza sativa L.) at the germination stage based on genome-wide association study - Ju, Chunyan; Ma, Xiaoding; Han, Bing; Zhang, Wei; Zhao, Zhengwu; Geng, Leiyue; Cui, Di; Han, Longzhi (Frontiers in Plant Science, 2022)
Salt stress affects rice seed germination and seedling formation, seriously restricting rice production. Screening salt-tolerant rice varieties and analyzing the genetic mechanisms underlying salt tolerance are therefore very important to ensure rice production. In this study, 313 Oryza sativa ssp. japonica germplasm were used to conduct a genome-wide association study (GWAS) using 1% NaCl as a salt stress treatment during germination stage. The germination potential (GP) on different days and the germination index (GI) under salt stress were used as salt tolerance indicators. The results of population structure analysis showed that the 313 germplasm studied could be divided into two subpopulations, consistent with the geographical origins of the materials. There were 52 loci significantly related to salt tolerance during germination, and the phenotypic contribution rate of 29 loci was > 10%. A region on chromosome 11 (17049672–17249672 bp) was repeatedly located, and the candidate gene LOC_Os11g29490, which encodes a plasma membrane ATPase, was identified in this locus. Further haplotype analysis showed the GP of germplasm with different haplotypes at that locus significantly differed under salt stress (p < 0.05), and germplasm carrying Hap2 displayed strong salt tolerance during the germination stage. Two other promising candidate genes for salt tolerance were identified: LOC_Os01g27170 (OsHAK3), which encodes a potassium transporter, and LOC_Os10g42550 (OsITPK5), which encodes an inositol 1, 3, 4-trisphosphate 5/6-kinase. The results of this study provide a theoretical basis for salt-tolerant gene cloning and molecular design breeding in rice.